Pengaruh Penggunaan Sistem Informasi Akuntansi dengan Konsep UTAUT Pada Kinerja Individual - Ardana, Komang Thica Frisma; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p18, 2018)
Competitive global competition create an organization needs to utilize accounting information system (AIS) to improve individual performance in the purpose of improving the whole organizational performance. This study examines the successful use of AIS using UTAUT concept. More specifically, this study aims at determin ing the influence of performance expectations, effort expectations, sociocultural factors (especially the Tri Hita Karana culture) and facilitating condition to the individual performance of AIS’s users. The research was conducted at Alam Kulkul Boutique Resort. The sample was taken using non probability s aturating sampling technique from 40 individuals. Data analysis technique applied a multiple linear regression analysis. The results of this study indicate that each variable includes performance expectation, socio-cultural factors and facilitating condition positively influence to individual performance, while effort expectations have no significant effect to the  individual performance. Keywords:   performance expectation, effort expectation, sosiocultural factor,  facilitating condition, individual performance